Collapse performance of seismically isolated buildings designed by the procedures of ASCE/SEI 7. (1st June 2018) - Kitayama, Shoma; Constantinou, Michael C.
Highlights: Investigated collapse performance of seismically isolated and non-isolated buildings. Buildings designed by the minimum ASCE 7 criteria and enhanced design criteria. Considered double and triple friction pendulum isolators. Probabilities of collapse in the maximum earthquake were calculated. Recommendations provided for system design to achieve acceptable performance. Abstract: This article presents an analytical study of the seismic collapse performance of seismically isolated buildings and comparable non-isolated buildings. The study is based on archetypical 6-story perimeter frame seismically isolated buildings designed with special concentrically braced frames (SCBF), ordinary concentrically braced frames (OCBF) and special moment resisting frames (SMF) for a location in California using the minimum criteria of ASCE/SEI 7-10 and ASCE/SEI 7-16 and also using a number of enhanced designs. The isolation system consists of triple Friction Pendulum (FP) isolators with stiffening behavior at large displacement. Additionally, double concave sliding isolators are considered and designed per minimum criteria of ASCE/SEI 7 and without a displacement restrainer, a practice permitted by the standards. Non-isolated structures, also with braced and moment frame configurations, are designed using the minimum criteria of ASCE/SEI 7 and studied. The study concludes that seismically isolated buildings designed by the minimum criteria of ASCE/SEI 7 of either 2010 or 2016 may have unacceptable probability of collapse in the Risk-Targeted Maximum Considered Earthquake (MCER ). The probability of collapse in the MCER becomes acceptable when they are designed with enhanced criteria of R I =1.0 and with isolators having a displacement capacity at initiation of stiffening equal to 1.5 times the demand in the MCER . It is also observed that designs that meet the minimum criteria of ASCE/SEI 7 of either 2010 or 2016 and without any displacement restrainer have unacceptably high probabilities of collapse.